Estilos de crianza parental y la inteligencia emocional en padres de niños de cuatro y cinco años institución educativa inicial Miguel Grau Seminario, distrito de Nauta provincia de Loreto 2022 - Gonzales Suarez, Betty Graciela (2023)
The research was aimed at verifying the association of parenting styles with emotional intelligence in parents of 4 and 5-year-old children Institucion Educativa Inicial Miguel Grau Seminario N° 60520, district Nauta Province of Loreto 2022. It is a confirmatory study descriptive design - correlational, crosssectional, with a population of 67 parents and a sample of 57 subjects, selected by stratified sampling by proportional and random allocation; the questionnaire was used as an instrument. The application of Spearman's Rho statistical test allowed us to verify that there is a significant relationship between parenting styles and the emotional intelligence of the parents who were subjects of the study sample (rs=0.724; Sig. <0.01). The inferential analysis of the dimensions made it possible to verify that there is a significant association between the authoritarian parenting style and emotional intelligence in the parents who were subjects of the sample (rs=0.584; Sig. <0.01). It was verified that there is a significant association between the democratic parenting style and emotional intelligence in the parents of the sample (rs=0.594; Sig. <0.01). Finally, it was determined that there is a significant association between the permissive parenting style and emotional intelligence in the parents of the sample (rs=0.411, Sig. <0.01).